"A Heart of Many Chambers": The Theological Hermeneutics of Legal Multivocality*. (6th February 2015) - Fraade, Steven D.
Abstract : Given the multiplicity of legal interpretations and opinions, the question of the place of legal debate within early rabbinic literature of late antiquity—both as textual practice and as hermeneutical and legal theory—has occupied a particularly busy space within recent scholarship. This question centers on several issues of broad significance for the history of rabbinic Judaism and its literature: Does this phenomenon (if we can speak of it in the singular) represent a defining characteristic of rabbinic culture overall, or rather an aspect better attributed to specific times, places, and rabbinic "schools"? Did it emerge and develop internally within rabbinic Judaism, or is it, on the one hand, the continuation of antecedents in the pre-rabbinic, late Second Temple period, or, on the other hand, the result of external influences or pressures (e.g., Greco-Roman or early Christian) of a later time? Does such legal multivocality reflect the actual nature of either/both rabbinic jurisprudence or/and pedagogy, or the editorial choices of the later anonymous redactors of the composite and anthological texts that have come down to us (or, as I shall demonstrate, both)? Finally, what are its hermeneutical and theological underpinnings (as well as sociopolitical ramifications)? While these four questions will frame what follows, it is the latter two that will particularly demand our attention. They will be addressed, whether explicitly or implicitly, in several comparative textual analyses that will constitute the body of this article.